Mortality, In-Hospital Morbidity, Care Practices, and 2-Year Outcomes for Extremely Preterm Infants in the United States, 2013-2018. Issue 4 (21st December 2022) - Bell, E.; Hintz, S.; Hansen, N.; Bann, C.; Wyckoff, M.; DeMaruo, S.; Walsh, M.; Vohr, B.; Stoll, B.; Carlo, W.; Van Meurs, K.; Rysavy, M.; et al.
Abstract : ( JAMA . 2022;327:248–263. doi: 10.1001/jama.2021.2358) While mortality rates of preterm infants have decreased over time, differences in age assessment, assessment instruments, and other factors have made determining neurodevelopmental outcomes difficult. This study used data collected from preterm infants born before the gestational age of 29 weeks between January 1, 2013 and December 31, 2018 from 19 network centers in the Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network.